Patent Evaluation Technology used in Automobile Steering Product Development - Jun CHEN; He HUANG (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Automobile steering product development is based on the research basis. By using the existing patent technology as an example is one of the effective ways to realize rapid product development. In this article, through similarity algorithm, the patent technology of car steering screening was selected, and then through the Analytic Hierarchy Process, the patent technology was analyzed to find the most suitable product development, and examples for the development of automobile steering products were provided. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2552